Characterization and properties of intermetallic Al3Ti alloy synthesized by reactive foil sintering in vacuum. Issue 17 (9th September 2016) - Wei, Ningxia; Han, Xiaoxiao; Zhang, Xueyi; Cao, Yang; Guo, Chunhuan; Lu, Zichuan; Jiang, Fengchun
Abstract: Abstract : A dense monolithic intermetallic Al3 Ti alloy was successfully synthesized via reactive sintering in vacuum using TC4 alloy and pure aluminum foils with appropriate initial thickness. Energy dispersive spectroscopy (EDS), x-ray diffractometry (XRD), and scanning electron microscopy (SEM) were used to characterize the phase and microstructure of Al3 Ti alloy. Ultrasonic measurement was performed to evaluate the physical property of Al3 Ti alloy. Different thermal analysis, thermogravimetry (TG) and differential scanning calorimetry (DSC) were used to assess the thermal property of Al3 Ti alloy. The compressive tests were carried out on a universal load frame to determine the mechanical properties, including the compressive strength and failure strain of the fabricated intermetallic Al3 Ti alloy. The current results indicated that the density of Al3 Ti alloy is slightly higher than the theoretical density, the average Young's modulus is lower than the theoretical value. A trace of aluminum in Al3 Ti alloy was detected, which is distinctly affected on the density, Young's modulus and mechanical properties of this titanium aluminide alloy. The stress–strain curves of Al3 Ti alloy shows a linear elastic behavior without any plastic deformation, and the fracture features are the mixed fracture of transgranular and intergranular. Some other fundamental physical and mechanical properties of the Al3 Ti alloy were also obtained in the present study.